The 2nd Baltic Osseointegration Academy and Lithuanian University of Health Sciences Consensus Conference 2019. Summary and Consensus Statements: Group I - Biological Aspects of Tooth Extraction, Socket Healing and Indications for Socket Preservation - Gintaras Juodzbalys; Povilas Daugela; Onurcem Duruel; Maria Helena Fernandes; Pedro de Sousa Gomes; Samir Goyushov,; Lorena Mariano; Lukas Poskevicius; Arturas Stumbras; Tolga Fikret Tözüm (eJournal of Oral Maxillofacial Research)
Introduction: The task of Group I was to review and update the existing data concerning the physiologic process of socket healing, in the absence or presence of grafting materials or platelet concentrates, addressing the associated molecular and cellular events that culminate in the restoration of the lost tissue architecture and functionality. The second task was to review current literature concerning extraction socket classification immediately following tooth extraction and the rationales for socket preservation/augmentation procedures and with reference to it suggest novel clinical decision tree for extraction socket preservation/augmentation in aesthetic and non-aesthetic area.